Metabolic redundancy and specialisation of novel sulfide-oxidizing Sulfurimonas and Sulfurovum along the brine-seawater interface of the Kebrit Deep - Rayyan Alamoudi; Alan Barozzi; Grégoire Michoud; Marc W. Van Goethem; Charlene Odobel; Yue Chen; Ramona Marasco; Daniele Daffonchio (Environmental Microbiome)
Abstract Background Members of the Campylobacterota phylum are dominant key players in sulfidic environments, where they make up a stable portion of sulfide-oxidizing bacterial communities. Despite the significance of these bacteria in primary production being well recognised in several ecosystems, their genomic and metabolic traits in sulfidic deep hypersaline anoxic basins (DHABs) remain largely unexplored. This knowledge gap not only hampers our understanding of their adaptation and functional role in DHABs but also their ecological interactions with other microorganisms in these unique ecosystems. Results Metabolic reconstructions from metagenome-assembled genomes (MAGs) of sulfide-oxidizing Campylobacterota were conducted at 10 cm spatial resolution within the halocline of the brine-seawater interface (BSI, salinity 91–155 PSU) of the 1466 m deep sulfidic Kebrit Deep in the Red Sea. Fifty-four Campylobacterota MAGs were assembled and dereplicated into three distinct groups, with the highest-quality genome retained as representative. These genomes represent novel sulfide-oxidizing species within the Sulfurimonas and Sulfurovum genera, which differ from those found in mildly saline deep-sea sulfidic pools. They are stratified along the BSI and utilise the reductive tricarboxylic acid cycle to fix carbon dioxide, acting as primary producers. Their energy generation processes include aerobic or anaerobic-nitrate-dependent sulfide oxidation, as well as hydrogen oxidation. In addition to the osmoprotectant pathways commonly observed in Campylobacterota, such as the synthesis and uptake of proline and glutamate, the two Kebrit Deep Sulfurovum species exhibit genomic signatures for ectoine synthesis, further aiding their adaptation to high salinity. This combination of metabolic redundancy and specialisation within the confined spatial boundaries (~1 m) of the BSI is pivotal in governing microbial interactions, including those with sulfate-reducers, heterotrophs, and other primary producers. Conclusions These results show how the selective pressures mediated by the sulfidic and hypersaline conditions of Kebrit Deep have resulted in novel, adapted and metabolically redundant Sulfurimonas and Sulfurovum species that contribute to the energy coupling, nutrient turnover and metabolic continuity along the physico-chemical gradient of the BSI.